The Effect of Deproteinized Bovine Bone Mineral on Saos-2 Cell Proliferation - Khojasteh, Arash; Ghahremani, Mohammad Hossein; Ostad, Seyed Nasser; Eslami, Mohammad; Motahhary, Pourya; Morad, Golnaz; Shidfar, Shireen (Iranian Endodontic Journal, 2013)
Introduction: Deproteinized bovine bone mineral (Bio-Oss) is a xenogenic bone substitute, widely used in maxillofacial bone regeneration. The aim of this in vitro study was to investigate its influence on the growth behavior of human osteosarcoma cell line, Saos-2 culture, and compare it with the physiologic dose of Dexamethasone, an inductive factor for osteoblasts. Materials and Methods: Human osteosarcoma cells, Saos-2, were cultured on Bio-Oss and their growth rate was compared to Saos-2 cultures treated with Dexamethasone 10-7 M in contrast to cells cultivated in PBS, in the control group. Assessment of proliferation was performed after 24, 36, and 48 hours by counting cells using trypan blue exclusion method. Alkaline phosphatase was measured spectrophotometrically at 405 nm with paranitrophenol buffer. Results: After 48 hours, the number of Saos-2 cells increased significantly when subcultured with Bio-Oss. Bio-Oss was more effective on the enhancement of proliferation of Saos-2 cells when compared to the physiologic dose of Dexamethasone (P<0.05). Alkaline phosphatase activity increased in cells grown on Bio-Oss and dexamethasone 10-7M in contrast to cells cultivated in PBS control group. The greatest level of activity was observed in the group containing Bio-Oss after 48 hour. Conclusion: The significant increase of cell proliferation and alkaline phosphatase activity in cells cultured on Bio-Oss, compared to Dexamethasone-treated cells, suggests the important role of this bone substitute in promoting bone regeneration.